PENGGUNAAN DAN BATAS DISKRESI DALAM PENGELOLAAN KEUANGAN DAERAH DI INDONESIA - Arbani, Tri Suhendra (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2019)
Regional finance is the most important thing and becomes the pulse in carrying out all regional government affairs. Regulation in the financial sector is important because many regional heads carry out transportation for corruption because they are wrong in managing and making policies that have no legal basis. In this paper, we try to examine problems such as the changing room for discretion and the discretionary limitation in managing regional finances. This type of research used in this paper is normative legal research, that is research conducted or based on written regulations and other legal materials related to secondary data. In this legal research is used to discuss: statute approach, comparative approach, and conceptual approach. The data analysis technique in writing uses data management in essence the activities to make a system of written legal materials. The results of this paper describe how you should use discretion. This concept of discretion comes in the middle of a weak system of registration of invitations and legal vacuum. In essence, government officials take discretionary measures if they ask for various terms and discussion spaces from the discretion itself that has been regulated in government administration laws. These restrictions on the use of discretion indicate that not everything can be taken as a discretionary measure. Using ermessen freis or discretion basically covers the use of ermessen freis cannot replace with the prevailing legal system (positive legal rules) and the use of ermessen freis is only in the public interest.